2022
DOI: 10.3390/foods11081128
|View full text |Cite
|
Sign up to set email alerts
|

Development of Healthier and Functional Dry Fermented Sausages: Present and Future

Abstract: In recent years, consumer perception about the healthiness of meat products has changed. In this scenario, the meat industry and the scientific and technological areas have put their efforts into improving meat products and achieving healthier and functional formulations that meet the demands of today’s market and consumers. This article aims to review the current functional fermented meat products, especially on sausage development. Firstly, an emphasis is given to reducing and replacing traditional ingredien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 107 publications
(140 reference statements)
0
20
0
Order By: Relevance
“…The starter culture should grow well under the physical and chemical conditions of the sausages and be harmless to humans. To ensure the safety of starter cultures, hemolysis, toxin production, and biogenic amine production by the microorganisms in the starter culture must be evaluated ( Jeong and Lee, 2015 ; Sirini et al, 2022 ). Some starter cultures produce biogenic amines in fermented sausages, and thus, starter cultures producing no biogenic amines need to be developed, and processing methods such as packaging, additives, hydrostatic pressure, and smoking can also reduce biogenic amines ( Doeun et al, 2017 ; Özogul and Hamed, 2018 ).…”
Section: Requirement For Starter Culture In Fermented Sausagesmentioning
confidence: 99%
“…The starter culture should grow well under the physical and chemical conditions of the sausages and be harmless to humans. To ensure the safety of starter cultures, hemolysis, toxin production, and biogenic amine production by the microorganisms in the starter culture must be evaluated ( Jeong and Lee, 2015 ; Sirini et al, 2022 ). Some starter cultures produce biogenic amines in fermented sausages, and thus, starter cultures producing no biogenic amines need to be developed, and processing methods such as packaging, additives, hydrostatic pressure, and smoking can also reduce biogenic amines ( Doeun et al, 2017 ; Özogul and Hamed, 2018 ).…”
Section: Requirement For Starter Culture In Fermented Sausagesmentioning
confidence: 99%
“…Besides phytosterols, many other bioactive compounds, such as dietary fibers, antioxidants, omega-3 and other polyunsaturated fatty acids have been suggested as being interesting functional ingredients that can be applied in the development of functional foods (Granato et al, 2020). Additionally, probiotics (ingested live microorganisms that induce health benefits in the host if added in adequate amounts) and prebiotics (selected substrates used by the beneficial host microorganisms) have received attention leading to their being among the most studied functional components (Comunian et al, 2021;Sirini et al, 2022). Moreover, the use of postbiotics, which are products or metabolic byproducts produced by probiotics when they consume prebiotics, has been tested in many applications in the food industry (Moradi et al, 2020).…”
Section: Food Fortification and Functional Foodsmentioning
confidence: 99%
“…According to Sirini and colleagues [ 6 ], recent studies have shown that there is consumer demand for healthier and functional formulations of meat products. Generally, cultured meat offers eclectic benefits and resolves financial, animal welfare, ethics, resource scarcity and general health issues [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%